AGROCHEMICAL PROPERTIES OF VIRGIN LIGHT SIEROZEMS SPREADED IN THE GUZOR MASSIF (Scientific journal of the Fergana State University, 2025)
The article defines the agrochemical properties of light sierozem soils common in the soil cover of the GTL plant and the Shortan gas complex in the Guzor massif of the Kashkadarya region. Soil humus, total nitrogen and phosphorus, mobile phosphorus increased from east to west and from north to south. It is noted that the soil environment (pH), on the contrary, decreases with weak alkalinity.